Making healthcare green : the role of Cloud, green IT, and data science to reduce healthcare costs and combat climate change /: the role of Cloud, green IT, and data science to reduce healthcare costs and combat climate change. ([2018]) - Godbole, Nina S; Lamb, John P
No abstract available